TINJAUAN YURIDIS PEMAIN JUDI ONLINE DI WILAYAH SIDOARJO - Apriyanto, Reditya; Haniyah, Haniyah (JURNAL LEGISIA, 2023)
The development of information technology has made a significant contribution to the improvement of welfare, the advancement of human civilization, and progress in various fields. On the other hand, information tech-nology can also be effectively used as a means to facilitate illegal activities, such as online gambling. This re-search aims to identify the factors causing online gambling in the Sidoarjo region and to understand the pre-ventive efforts and the application of criminal sanctions against online gambling players in that area. This re-search adopts a non-doctrinal legal approach with socio-legal approach. The data sources used are both sec-ondary and primary. Secondary data is obtained from books, journal articles, and relevant theses. Primary da-ta is acquired through informants from the Sidoarjo Police Department. Data collection techniques involve in-terviews and observations. Data analysis is conducted using descriptive analytical approach and employs em-pirical concepts to explain the legal prevention mechanisms against online gambling. The research findings indicate that the causes of online gambling in the Sidoarjo region are attributed to factors lack of faith and devotion to God, economic difficulties, and cultural habits. Preventive measures and law enforcement against online gambling players in the Sidoarjo region include collaboration with the Ministry of Information and Electronics to block websites involved in online gambling. Prevention is also conducted through educating the public about the negative effects of electronic media on psychological well-being and behavior. Law enforce-ment is based on Article 27 Paragraph (2) of Law Number 11 of 2008 concerning electronic information and transactions.